Let the sea resound - Otis, George Jr. ([Lynnwood, Wash.] : Sentinel Group, 2004)
Documentary that covers the astonishing revival that is currently sweeping through the nation of Fiji. It shows how Fiji has become a nation of unprecedented Christian unity, contemporary signs and wonders, rapid church growth and genuine socio-political transformation.
Title from disc label.
Extras: Fiji - brief history, speeches & documents, maps; Behind the scenes; Resources; Teaching on unity - video teaching by Rev. Suliasi Kurulo (ca. 30 min.).
Executive producer, writer and director, George Otis, Jr.; editors, Jarod Pace and Mark Morache
Keywords: Fiji -- Religion; Fiji -- History; Fiji -- Politics and government